Homologous recombination proficient subtypes of high-grade serous ovarian cancer: treatment options for a poor prognosis group - Stiegeler, Nadja; Garsed, Dale W.; Au-Yeung, George; Bowtell, David D. L.; Heinzelmann-Schwarz, Viola; Zwimpfer, Tibor A. (Frontiers in Oncology, 2024)
Approximately 50% of tubo-ovarian high-grade serous carcinomas (HGSCs) have functional homologous recombination-mediated (HR) DNA repair, so-called HR-proficient tumors, which are often associated with primary platinum resistance (relapse within six months after comple-tion of first-line therapy), minimal benefit from poly(ADP‐ribose) polymerase (PARP) inhibi-tors, and shorter survival. HR-proficient tumors comprise multiple molecular subtypes includ-ing cases with CCNE1 amplification, AKT2 amplification or CDK12 alteration, and are often characterized as “cold” tumors with fewer infiltrating lymphocytes and decreased expression of PD-1/PD-L1. Several new treatment approaches aim to manipulate these negative prognostic features and render HR-proficient tumors more susceptible to treatment. Alterations in multiple different molecules and pathways in the DNA damage response are driving new drug devel-opment to target HR-proficient cancer cells, such as inhibitors of the CDK or P13K/AKT path-ways, as well as ATR inhibitors. Treatment combinations with chemotherapy or PARP inhibi-tors and agents targeting DNA replication stress have shown promising preclinical and clinical results. New approaches in immunotherapy are also being explored, including vaccines or anti-body drug conjugates. Many approaches are still in the early stages of development and further clinical trials will determine their clinical relevance. There is a need to include HR-proficient tumors in ovarian cancer trials and to analyze them in a more targeted manner to provide further evidence for their specific therapy, as this will be crucial in improving the overall prognosis of HGSC and ovarian cancer in general.